PENINGKATAN HASIL BELAJAR SISWA PADA PEMBELAJARAN TEMATIK DENGAN TEMA PERISTIWA DALAM KEHIDUPAN MELALUI MODEL PEMBELAJARAN INSTANT ASSESMENT DENGAN MEDIA CHOOSE NUMBER DI KELAS V SDN 06 LUBUK JANTAN - Adriati, Adriati (STKIP Pesisir Selatan, 2019)
Based on the learning outcomes of Class V students of SDN 06 Lubuk Jantan in thematic learning with the theme of Events in Life it was found that many student learning outcomes in Thematic Learning were still incomplete. The purpose of this study was to describe and obtain information about improving student learning outcomes in Thematic Learning with the Theme of Events in Life through the Instant Assessment Learning model with the Media Choose Number in Class V of SDN 06 Lubuk Jantan. This research is a classroom action research. The research procedures in this study include planning, action, observation and reflection. This study consisted of two cycles with four meetings. The subject of the study consisted of 25 students of Class V SDN 06 Lubuk Jantan. The research data was collected using a test sheet. Data were analyzed using percentages. Based on the results of the research and discussion that have been put forward, it can be concluded that the learning model of Instant Assessment Learning Model using media choose number can improve student learning outcomes in Thematic Learning with the Theme of Events in Life in Class V SDN 06 Lubuk Jantan. Student learning outcomes in the first cycle were 72.90 increased to 83.87 with an increase of 10.97%.